A study of the factors that cause delays in import cargo clearance case study : Greenpen Freight Services Sdn. Bhd. / Zakhirah Haji Awang - Awang, Zakhirah (1997)
This graduation exercise has been written to provide a clear view a practical overall understanding the operation of forwarding agents. In particularly, it covers the import cargo clearance process, the problem that caused a delay in import cargo clearance process. Also study the effect from the problems arise. Personal interview and observations are made to gather the data. From the findings, it was founds that there was a problem caused a delay in cargo clearance. The problems are not comes from one party but its comes from all the party that involve in the process of cargo clearance, such as, customs, forwarders, shipping agent, haulier, and port authority. Based on the problems occurred, some recommendation is made in order to establish the more efficient, effective and systematic in import cargo clearance.